Power losses analysis for reduced switch 9-level cascaded H-bridge multilevel inverter - Ismail, Mohammad Haziq; Isa, Zainuddin Mat; Arshad, Mohd Hafiz; Mid, Ernie Che; Ismail, Baharuddin; Talib, Md Hairul Nizam (Institute of Advanced Engineering and Science, 2024)
This study provides a thorough examination of power losses and total harmonic distortion (THD) in single-phase 9-level cascaded H-bridge multilevel inverters (CHB MLI) at low switching frequencies. The aim is to analyze the efficiency of a single-phase 9-level cascaded CHB MLI using three distinct switch configurations: 16-switch, 11-switch, and proposed 8-switch. The calculated switching angles are optimized using the feed-forward methodology. Two types of load conditions—R load and R-L load—are being examined. The results suggest that the proposed 8-switch design exhibits superior efficiency by limiting power losses compared to other topologies. Regarding THD, the conventional topology yields a somewhat lower value, however, the disparity is less than 1% when compared to both reduced switch topologies.